Lithuanian Phraseological Names of Belemnite - Jasiūnaitė, Birutė (Slavistica Vilnensis, 2009)
The article analyzes rare Lithuanian phraseological names of belemnite. Such linguistic stereotypes cannot be described outside the bounds of ethnography, folklore and other trends in Lithuanian ethnic culture.